Post-Soviet Russia as a Product of Half-Disintegration of the USSR: Facts and Interpretation. (July 2022) - Epstein, David
The article shows the interconnection in the development of social and economic institutes of the USSR and post-soviet Russia and that on the post-Soviet space and in the Russian Federation a system of the semi-peripheral oligarchic bureaucratic capitalism has occurred, of which an economic stagnation is typical. The author proposes a review of the statistical data of three post-soviet evolution stages (1992–1998, 1999–2007, from 2008 until now), the causes of the economic decline of the 1990s, with accentuating the degradation of the technological basis and growing social contradictions, negative economic, and demographic consequences. The causes of negative evolution of Russia's economy and society are shown. The answer is given to the questions: (1) what social forces were behind the reforms in the USSR and what social forces took over the power after the USSR vanished and (2) why Russia became a dependent, semi-peripheral part of the global economic system.